2015
DOI: 10.4012/dmj.2014-202
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of orthodontic wires made of super engineering plastic

Abstract: Most orthodontic equipment is fabricated from alloys such as stainless steel, Co-Cr and Ni-Ti because of their excellent elastic properties. In recent years, increasing esthetic demands, metal allergy and interference of metals with magnetic resonance imaging have driven the development of non-metallic orthodontic materials. In this study, we assessed the feasibility of using three super engineering plastics (PEEK, PES and PVDF) as orthodontic wires. PES and PVDF demonstrated excellent esthetics, although PEEK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 15 publications
2
42
0
2
Order By: Relevance
“…PEEK has excellent mechanical properties, for example, creep resistance, low water absorption and high fracture resistance [1][2][3][4] . It has been proposed as a functional and esthetic metalfree material in various dental applications, such as implants 5) , temporary abutments 6,7) , orthodontic wires 8) , removable prostheses 9) and fixed prostheses 10) . Veneering resins are recommended to cover the underneath grayish and opaque color of PEEK-based restorations to mimic the natural tooth appearance 11) .…”
Section: Introductionmentioning
confidence: 99%
“…PEEK has excellent mechanical properties, for example, creep resistance, low water absorption and high fracture resistance [1][2][3][4] . It has been proposed as a functional and esthetic metalfree material in various dental applications, such as implants 5) , temporary abutments 6,7) , orthodontic wires 8) , removable prostheses 9) and fixed prostheses 10) . Veneering resins are recommended to cover the underneath grayish and opaque color of PEEK-based restorations to mimic the natural tooth appearance 11) .…”
Section: Introductionmentioning
confidence: 99%
“…Five were clinical reports [2,6,8,18,24] and 35 were papers on PEEK surface treatments [13][14][15][16][17] how the bioactivity of PEEK can be improved [1,21]; the characteristics of CFR-PEEK [3,7,[19][20]; the biocompatibility of PEEK [5]; PEEK applications [4,8,[10][11]30]; PEEK biofilm formation [22,[31][32][33][34], PEEK as an abutment material and as an implant material [12,23,[25][26][27][28][29]35,40] and the use of CAD-CAM with PEEK [36][37][38][39]. …”
Section: Literature Search and Resultsmentioning
confidence: 99%
“…Unlike metal, PEEK is biocompatible and has a natural tooth-colored appearance, hence its widespread use in implants, provisional abutments, implant supported bars, or clamp materials in the field of removable dental prostheses and maxillary obturator prostheses [9][10][11]. PEEK also offers an alternative to orthodontic wires for reasons of improved aesthetics, allergies to metals, and interference of metals with TC [10].…”
Section: Dental Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research 40 has demonstrated the highquality physical properties of PEEK. A PEEK tube was developed as an auxiliary device to help make orthodontic treatment more efficient and to satisfy consumer esthetic demands.…”
Section: Discussionmentioning
confidence: 99%